Kajian Komparatif Numeralia Satu dalam Bahasa Melayu Papua dengan Prefiks Se- Bahasa Indonesia - Supardi Supardi (Kibas Cenderawasih : Jurnal Ilmiah Kebahasaan dan Kesastraan, 2019)
This paper analyzes the numerals satu in Melayunese of Papua. The mayor theory applied is numerals categories. This numerlia is the meaning one. This numeralia in Indonesianese as like prefix se- also composed with all kinds of category, likes: nomina, verb, adverbia, adjectiva, and numerals, not only nominal.The meaning of satu not only one, but olso a or an, some, sometime (after arirved), ad so on. Composite by numeralia satu ‘one’  were uncountable numerals, or not countable. The structures numeralia satu of Melayu Papua is satu ‘one’. The structures of numralia satu ‘one’ in bahasa Indonesia same with prefiks se-.